2009
DOI: 10.2478/v10077-009-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Thermal Spraying Ni-Al Alloy Coatings

Abstract: The article presents the results of testing of Ni-Al alloy coatings with different chemical and phase composition, which might replace currently used electrolytic chromium coatings. Crust chromium coatings are suitable for reconditioning of machine parts because of their very good maintenance properties. However, due to toxicity of electrolytic chromium bath, their application tends to be restricted. Thermal flame and plasma spraying technologies were chosen for nickel aluminium coating application. Obtained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 8 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…Starosta et al produced NiAl coatings with the aim to possibly use them to replace currently used electrolytic chromium coatings and compared their microstructure and corrosion behaviour with that sprayed by flame spraying. Also the corrosion potential and current density values were evaluated for different Al concentrations in NieAl coatings tested in 0.01 M H 2 SO 4 electrolite solution at ambient temperature [127]; it is observed that the higher aluminium content causes a decrease of current densities.…”
Section: High Velocity Oxygen Fuel (Hvof) and Atmospheric Plasma Spray mentioning
confidence: 99%
See 2 more Smart Citations
“…Starosta et al produced NiAl coatings with the aim to possibly use them to replace currently used electrolytic chromium coatings and compared their microstructure and corrosion behaviour with that sprayed by flame spraying. Also the corrosion potential and current density values were evaluated for different Al concentrations in NieAl coatings tested in 0.01 M H 2 SO 4 electrolite solution at ambient temperature [127]; it is observed that the higher aluminium content causes a decrease of current densities.…”
Section: High Velocity Oxygen Fuel (Hvof) and Atmospheric Plasma Spray mentioning
confidence: 99%
“…The unique D-gun coatings found in the literature are those already presented in the FeAl section for Senderowski et al, who used NiAl and NiCr as bond coatings for FeAl [88,89]. Flame Spray: NiAl coatings can be regarded as substitutes of electrolytic chromium coatings [127,134]. Flame spray coatings are reported to show about 10 times larger corrosion current density when compared with plasma spray coatings; they concluded that the structure and chemical constitution of coatings greatly influences the value of corrosion potential (E corr ) and, the more aluminium content the lower E corr .…”
Section: Thermal Spraying Of Nieal By Other Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the alloys based on Ni 3 Al may offer significant advantages because of the attractive combination of the properties. Ni 3 Al is very resistant to heat and corrosion, and finds use in heat-treating furnaces and other applications where its longer lifespan and reduced corrosion give it an advantage over stainless steel [3]. However, commercial use of nickel aluminides is limited due to low ductility and toughness of the aluminides at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Some processing problems may intensify these obstacles such as: the exothermic nature of formation of nickel aluminides and high difference in the melting point of Al and Ni. Microstructural modifications are processing routes which can overcome part of mentioned problems [3,4]. One of the effective techniques for preparing nanocomposite powders consisting of more than two phases is mechanochemical synthesis.…”
Section: Introductionmentioning
confidence: 99%